Atuação do Farmacêutico com Impacto do Acompanhamento Farmacoterapêutico aos Pacientes Portadores de Diabetes Mellitus Tipo 2: Uma Revisão Sistemática - Repolho, Kerlle Thevola Ferreira (Brasil, 2019)
Diabetes Mellitus (DM) is a metabolic disease with hyperglycaemic characteristic, which triggers complications in the function of various organs like the kidneys, eyes, heart, nerves, brain and blood vessels. In Brazil, about 12.5 million people are diagnosed as having DM, and it ranks fourth among the ten countries with the highest number of people with DM. More than 2 million cases of DM2 are registered every year in Brazil. This pathology has generated a high social and financial cost to the patient and to the health system, besides the DM2 brings severe complications being the main causes of morbidity and mortality of diabetic patients. The objective of this study was to carry out a review of the literature on Pharmacotherapeutic Accompaniment for adult patients with Type 2 Diabetes Mellitus, to demonstrate its impact on the life of these patients and to present the pharmacist's performance in this regard. The present study is a literature review of the systematic type of articles included since the 2007 period in three databases, with the inclusion criteria were the correlations with the descriptors: Pharmacotherapeutic Monitoring, Diabetes Mellitus type 2. Many articles showed high frequency of PRM4, lack of physical activity and lack of adequate diet. The articles demonstrated that they obtained positive results with the Pharmacotherapeutic Monitoring if it proved to be efficient for the therapy of diabetics.